Supine versus Prone Percutaneous Nephrolithotomy for Complex Stones: A Multicenter Randomized Controlled Trial - Perrella, Rodrigo; Vicentini, Fabio C.; Paro, Eliane D.; Torricelli, Fabio C. M.; Marchini, Giovani S.; Danilovic, Alexandre; Batagello, Carlos A.; Mota, Priscila K. V.; Ferreira, Daniel B.; Cohen, David J.; Murta, Claudio B.; Claro, Joaquim F. A.; et al. (The Journal of urology, 2022)
Purpose:High-quality evidence comparing supine to prone percutaneous nephrolithotomy (PCNL) for the treatment of complex stones is lacking. This study aimed to compare the outcomes of supine position (SUP) and prone position (PRO) PCNL.Materials and Methods:A noninferior randomized controlled trial was performed according to the CONSORT (Consolidated Standards for Reporting Trials) criteria. The inclusion criteria were patients over 18 years of age with complex stones. SUP was performed in the Barts flank-free modified position. Except for positioning, all the surgical parameters were identical. The primary outcome was the difference in the success rate on the first postoperative day (POD1) between groups. The secondary outcome was the difference in the stone-free rate (SFR) on the 90th postoperative day (final SFR). A noninferiority margin of 15% was used. Demographic, operative, and safety variables were compared between the groups. Statistical significance was set at p <0.05.Results:Overall, 112 patients were randomized and their demographic characteristics were comparable. The success rates on POD1 were similar (SUP: 62.5% vs PRO: 57.1%, p=0.563). The difference observed (−5.4%) was lower than the predefined limit. The final SFRs were also similar (SUP: 55.4% vs PRO: 50.0%, p=0.571). SUP had a shorter operative time (mean±SD 117.9±39.1 minutes vs 147.6±38.8 minutes, p <0.001) and PRO had a higher rate of Clavien ≥3 complications (14.3% vs 3.6%, p=0.045).Conclusions:Positioning during PCNL for complex kidney stones did not impact the success rates; consequently, both positions may be suitable. However, SUP might be associated with a lower high-grade complication rate.